Novel antibacterial composite material and preparation method thereof
By preparation of composite antibacterial materials, the use of silicon dioxide dissipation and cross -linking to adsorb nano -oxide particles to form modified gas gel, and mix with polypropylene and other materials to solve the existing composite type The complexity and cost of antibacterial materials have achieved high -efficiency, low -cost antibacterial composite materials, and improved the performance and function of materials.
Patent Information
- Application Number
- CN202411457965.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing composite antibacterial materials have complex preparation processes, difficult reaction conditions and high raw material costs, resulting in low production costs and process efficiency.
Mix the use of metharxylsiline, water -free ethanol, and removal water, prepare silica solution under citric acid and temperature conditions, and then add nano -calcium calcium oxide and sodium polyacryl. , Adsorbing fixed nano -oxide particles, forming modified gas gel, combined with polypropylene and other materials for dual screw extrusion machine melting and squeezing, preparing new antibacterial composite materials.
It simplifies the production process, reduces production costs, improves the antibacterial and antibacterial effects, and enhances the compatibility and functional performance of composite materials, such as thermal insulation, sound insulation and noise reduction, earthquake resistance, fire protection, etc.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial materials, and specifically relates to a novel antibacterial composite material and a preparation method thereof. Background Art
[0002] Antibacterial materials refer to materials that have antibacterial properties or can be antibacterial and antimicrobial after antibacterial treatment. They can be used in food, medical and construction fields. Antibacterial materials can be divided into organic antibacterial materials, inorganic antibacterial materials and composite antibacterial materials. Organic antibacterial materials include natural antibacterial materials such as chitin, chitosan and its derivatives extracted from animals and plants, and synthetic organic antibacterial materials such as quaternary ammonium salts and biguanides; inorganic antibacterial materials are nano-scale antibacterial materials that are composited with ions, oxides or photocatalytic materials of transition metals such as silver, copper and zinc with antibacterial properties using inorganic materials as carriers; composite antibacterial materials are antibacterial materials obtained by combining inorganic nanoparticles and polymer organic bodies, which can exert the antibacterial effects of both, reduce the cytotoxicity of metal ions, and have good biocompatibility. However, the existing composite antibacterial materials have the disadvantages of complex preparation process, difficult to control reaction conditions, and high raw material costs. Therefore, composite antibacterial materials are the focus of current research and development of antibacterial materials. Summary of the invention
[0003] In view of the above shortcomings, the present invention discloses a novel antibacterial composite material and a preparation method thereof, which not only produces an antibacterial composite material with excellent antibacterial and antifungal effects, but also simplifies the production process and reduces production costs.
[0004] The present invention is achieved by adopting the following technical solutions: A novel antibacterial composite material comprises the following raw material components in parts by weight: 50-80 parts of polypropylene, 20-40 parts of nano calcium oxide, 10-20 parts of methyltriethoxysilane, 100-150 parts of anhydrous ethanol, 20-40 parts of deionized water, 2-5 parts of citric acid, 2-5 parts of sodium polyacrylate, 1-3 parts of benzoyl peroxide, 1-3 parts of polyvinyl alcohol, 1-3 parts of wetting agent, 1-3 parts of defoaming agent and 1-3 parts of chain extender.
[0005] Furthermore, the particle size of the nano calcium oxide is 10 to 30 nm.
[0006] Furthermore, the wetting agent is any one of polyethylene glycol ether and sodium dodecylbenzene sulfonate or a combination of two thereof.
[0007] Furthermore, the defoaming agent is any one of pentaerythritol stearate and polyoxypropylene oxyethylene glycerol ether or a combination of two thereof.
[0008] Furthermore, the chain extender is any one or more combinations of diethyltoluenediamine, glycidyl methacrylate and trimethylolpropane triacrylate.
[0009] The preparation method of the novel antibacterial composite material comprises the following steps: (1) Weighing each raw material component according to the ratio, mixing methyltriethoxysilane, half of anhydrous ethanol and deionized water under stirring conditions, then adding citric acid and reacting at a temperature of 50 to 60°C for 2 to 3 hours, then adding nano calcium oxide and sodium polyacrylate and continuing to react for 2 to 3 hours, then adding the remaining anhydrous ethanol and aging for 8 to 10 hours to obtain a wet gel; (2) drying the wet gel obtained in step (1) at 60° C. for 3 to 4 hours, then heating to 150 to 200° C. and keeping the temperature constant for 10 to 15 minutes, then heating to 500 to 600° C. and keeping the temperature constant for 30 to 45 minutes, and naturally cooling to room temperature to obtain an aerogel; (3) The aerogel, polypropylene, polyvinyl alcohol, wetting agent and defoaming agent obtained in step (2) are mixed evenly, and then benzoyl peroxide and chain extender are added, stirred and mixed, and then sent to a twin-screw extruder for melt blending and extrusion, followed by cooling, air drying and granulation to obtain a new antibacterial composite material.
[0010] Furthermore, the stirring speed in step (1) is 30 to 50 r / min.
[0011] Furthermore, in step (2), the temperature is heated to 150-200°C at a rate of 3-5°C / min, and then heated to 500-600°C at a rate of 1-3°C / min. By controlling the heating rate, the temperature can be prevented from changing too fast or too much, which would cause uneven heating of the aerogel, damage the internal structure of the aerogel, and reduce its performance.
[0012] Furthermore, the stirring speed in step (3) is 200 to 300 r / min.
[0013] Furthermore, the extrusion temperature of the twin-screw extruder in step (3) is 180-220° C., and the rotation speed is 400-500 r / min.
[0014] Compared with the prior art, this technical solution has the following beneficial effects: 1. The present invention firstly mixes methyltriethoxysilane, anhydrous ethanol and deionized water, prepares silica sol under citric acid and certain temperature conditions, then adds nano calcium oxide and sodium polyacrylate, uses silica sol to disperse and uniformly adsorb nano calcium oxide particles, and simultaneously uses sodium polyacrylate to cross-link with nano calcium oxide and silica sol respectively to promote the adsorption and fixation of nano calcium oxide particles and silica sol, and then stepwise dries and sinters the obtained wet gel to obtain modified aerogel, and then mixes the modified aerogel with polypropylene, polyvinyl alcohol, a wetting agent, a defoaming agent and a After the benzoyl peroxide and the chain extender are stirred and mixed, they are sent to a twin-screw extruder for melt blending and extrusion, and after cooling, air drying and granulation, a novel antibacterial composite material is obtained. Compared with directly mixing polypropylene and nano calcium oxide, the modified aerogel prepared by mixing nano calcium oxide and silica sol is mixed with polypropylene, and the modified aerogel has better compatibility with polypropylene, so that the nano calcium oxide can be evenly mixed with the polypropylene, which is beneficial for the composite material to play an antibacterial role by releasing calcium ions, and the addition of aerogel can also improve the thermal insulation, sound insulation and noise reduction, earthquake resistance, fire prevention and other functions of the composite material.
[0015] 2. The process of the present invention is simple, easy to operate, highly controllable, and suitable for large-scale and automated production. DETAILED DESCRIPTION
[0016] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.
[0017] Embodiment 1: A novel antibacterial composite material comprises the following raw material components in parts by weight: 60 parts of polypropylene, 25 parts of nano calcium oxide, 12 parts of methyltriethoxysilane, 120 parts of anhydrous ethanol, 30 parts of deionized water, 3 parts of citric acid, 3 parts of sodium polyacrylate, 2 parts of benzoyl peroxide, 1.5 parts of polyvinyl alcohol, 1.5 parts of wetting agent, 2 parts of defoaming agent, and 1.5 parts of chain extender; The particle size of the nano calcium oxide is 15 nm; the wetting agent is polyethylene glycol ether; the defoaming agent is pentaerythritol stearate; and the chain extender is diethyltoluenediamine.
[0018] The method for preparing the novel antibacterial composite material described in this embodiment comprises the following steps: (1) Weigh the raw material components according to the ratio, mix methyltriethoxysilane, half of the anhydrous ethanol and deionized water under stirring at a speed of 40 r / min, then add citric acid and react at a temperature of 53°C for 2.5 hours, then add nano calcium oxide and sodium polyacrylate and continue to react for 2.5 hours, then add the remaining anhydrous ethanol and age for 9 hours to obtain a wet gel; (2) drying the wet gel obtained in step (1) at 60°C for 3.5h, then heating to 160°C at a rate of 3.5°C / min, then heating to 550°C at a rate of 1.5°C / min and keeping the temperature constant for 35min, and naturally cooling to room temperature to obtain an aerogel; (3) The aerogel, polypropylene, polyvinyl alcohol, wetting agent and defoaming agent obtained in step (2) are mixed uniformly, and then benzoyl peroxide and chain extender are added and mixed under stirring conditions at a speed of 250 r / min, and then sent to a twin-screw extruder for melt blending and extrusion, followed by cooling, air drying and granulation to obtain a novel antibacterial composite material; the extrusion temperature of the twin-screw extruder is 200° C. and the rotation speed is 450 r / min.
[0019] Embodiment 2: A novel antibacterial composite material comprises the following raw material components in parts by weight: 50 parts of polypropylene, 20 parts of nano calcium oxide, 10 parts of methyltriethoxysilane, 100 parts of anhydrous ethanol, 20 parts of deionized water, 2 parts of citric acid, 2 parts of sodium polyacrylate, 1 part of benzoyl peroxide, 1 part of polyvinyl alcohol, 1 part of wetting agent, 1 part of defoaming agent, and 1 part of chain extender; The particle size of the nano calcium oxide is 10 nm; the wetting agent is obtained by mixing polyethylene glycol ether and sodium dodecylbenzene sulfonate in equal volumes; the defoaming agent is polyoxypropylene oxyethylene glycerol ether; and the chain extender is obtained by mixing diethyltoluenediamine and glycidyl methacrylate in equal volumes.
[0020] The method for preparing the novel antibacterial composite material described in this embodiment comprises the following steps: (1) Weigh the raw material components according to the ratio, mix methyltriethoxysilane, half of the anhydrous ethanol and deionized water under stirring at a speed of 30 r / min, then add citric acid and react at a temperature of 50°C for 2 hours, then add nano calcium oxide and sodium polyacrylate and continue to react for 2 hours, then add the remaining anhydrous ethanol and age for 8 hours to obtain a wet gel; (2) drying the wet gel obtained in step (1) at 60°C for 3 h, then heating to 150°C at a rate of 3°C / min, then heating to 500°C at a rate of 1°C / min and keeping the temperature constant for 30 min, and naturally cooling to room temperature to obtain an aerogel; (3) The aerogel, polypropylene, polyvinyl alcohol, wetting agent and defoaming agent obtained in step (2) are mixed evenly, and then benzoyl peroxide and chain extender are added and mixed under stirring conditions at a speed of 200 r / min, and then sent to a twin-screw extruder for melt blending and extrusion, followed by cooling, air drying and granulation to obtain a novel antibacterial composite material; the extrusion temperature of the twin-screw extruder is 180° C. and the rotation speed is 400 r / min.
[0021] Embodiment 3: A novel antibacterial composite material comprises the following raw material components in parts by weight: 70 parts of polypropylene, 35 parts of nano calcium oxide, 18 parts of methyltriethoxysilane, 140 parts of anhydrous ethanol, 35 parts of deionized water, 4 parts of citric acid, 4.5 parts of sodium polyacrylate, 2.5 parts of benzoyl peroxide, 2.5 parts of polyvinyl alcohol, 2.5 parts of wetting agent, 2.5 parts of defoaming agent, and 2.5 parts of chain extender; The particle size of the nano calcium oxide is 20 nm; the wetting agent is sodium dodecylbenzene sulfonate; the defoaming agent is polyoxypropylene oxyethylene glycerol ether; and the chain extender is trimethylolpropane triacrylate.
[0022] The method for preparing the novel antibacterial composite material described in this embodiment comprises the following steps: (1) Weigh the raw material components according to the ratio, mix methyltriethoxysilane, half of the anhydrous ethanol and deionized water under stirring at a speed of 40 r / min, then add citric acid and react at a temperature of 58°C for 2.5 hours, then add nano calcium oxide and sodium polyacrylate and continue to react for 2.5 hours, then add the remaining anhydrous ethanol and age for 9 hours to obtain a wet gel; (2) drying the wet gel obtained in step (1) at 60°C for 3.5h, then heating to 180°C at a rate of 4.5°C / min, then heating to 520°C at a rate of 2.5°C / min, keeping the temperature constant for 40min, and naturally cooling to room temperature to obtain an aerogel; (3) The aerogel, polypropylene, polyvinyl alcohol, wetting agent and defoaming agent obtained in step (2) are mixed evenly, and then benzoyl peroxide and chain extender are added and mixed under stirring conditions at a speed of 250 r / min, and then sent to a twin-screw extruder for melt blending and extrusion, followed by cooling, air drying and granulation to obtain a novel antibacterial composite material; the extrusion temperature of the twin-screw extruder is 190° C. and the rotation speed is 450 r / min.
[0023] Example 4: A novel antibacterial composite material, comprising the following raw material components in parts by weight: 80 parts of polypropylene, 40 parts of nano calcium oxide, 20 parts of methyltriethoxysilane, 150 parts of anhydrous ethanol, 40 parts of deionized water, 5 parts of citric acid, 5 parts of sodium polyacrylate, 3 parts of benzoyl peroxide, 3 parts of polyvinyl alcohol, 3 parts of wetting agent, 3 parts of defoaming agent, and 3 parts of chain extender; The particle size of the nano calcium oxide is 30 nm; the wetting agent is polyethylene glycol ether; the defoaming agent is obtained by mixing pentaerythritol stearate and polyoxypropylene oxyethylene glycerol ether in equal volumes; and the chain extender is glycidyl methacrylate.
[0024] The method for preparing the novel antibacterial composite material described in this embodiment comprises the following steps: (1) Weigh the raw material components according to the ratio, mix methyltriethoxysilane, half of the anhydrous ethanol and deionized water under stirring at a speed of 50 r / min, then add citric acid and react at a temperature of 60°C for 3 hours, then add nano calcium oxide and sodium polyacrylate and continue to react for 3 hours, then add the remaining anhydrous ethanol and age for 10 hours to obtain a wet gel; (2) drying the wet gel obtained in step (1) at 60°C for 4 h, then heating to 200°C at a rate of 5°C / min, then heating to 600°C at a rate of 3°C / min, keeping the temperature constant for 45 min, and naturally cooling to room temperature to obtain an aerogel; (3) The aerogel, polypropylene, polyvinyl alcohol, wetting agent and defoaming agent obtained in step (2) are mixed uniformly, and then benzoyl peroxide and chain extender are added and mixed under stirring conditions at a speed of 300 r / min, and then sent to a twin-screw extruder for melt blending and extrusion, followed by cooling, air drying and granulation to obtain a novel antibacterial composite material; the extrusion temperature of the twin-screw extruder is 220°C and the rotation speed is 500 r / min.
[0025] Comparative Example 1: A novel antibacterial composite material, comprising the following raw material components in parts by weight: 60 parts of polypropylene, 5 parts of nano silver oxide, 1.5 parts of polyvinyl alcohol, 1.5 parts of wetting agent, 2 parts of defoaming agent, and 1.5 parts of chain extender; The particle size of the nano calcium oxide is 15 nm; the wetting agent is polyethylene glycol ether; the defoaming agent is pentaerythritol stearate; and the chain extender is diethyltoluenediamine.
[0026] The preparation method of the novel antibacterial composite material described in this comparative example is as follows: weigh the raw material components according to the ratio, mix nano calcium oxide, polypropylene, polyvinyl alcohol, wetting agent and defoaming agent evenly, then add the chain extender and mix under the stirring condition of 250r / min, send to a twin-screw extruder for melt blending and extrusion, and then obtain the novel antibacterial composite material after cooling, air drying and granulation; the extrusion temperature of the twin-screw extruder is 200°C and the rotation speed is 450r / min.
[0027] Comparative Example 2: A novel antibacterial composite material, comprising the following raw material components in parts by weight: 60 parts of polypropylene, 25 parts of nano calcium oxide, 1.5 parts of polyvinyl alcohol, 1.5 parts of wetting agent, 2 parts of defoaming agent, and 1.5 parts of chain extender; The particle size of the nano calcium oxide is 15 nm; the wetting agent is polyethylene glycol ether; the defoaming agent is pentaerythritol stearate; and the chain extender is diethyltoluenediamine.
[0028] The preparation method of the novel antibacterial composite material described in this comparative example is as follows: weigh the raw material components according to the ratio, mix nano calcium oxide, polypropylene, polyvinyl alcohol, wetting agent and defoaming agent evenly, then add the chain extender and mix under the stirring condition of 250r / min, send to a twin-screw extruder for melt blending and extrusion, and then obtain the novel antibacterial composite material after cooling, air drying and granulation; the extrusion temperature of the twin-screw extruder is 200°C and the rotation speed is 450r / min.
[0029] Comparative Example 3: A novel antibacterial composite material, comprising the following raw material components in parts by weight: 60 parts of polypropylene, 25 parts of nano calcium oxide, 12 parts of methyltriethoxysilane, 120 parts of anhydrous ethanol, 30 parts of deionized water, 3 parts of citric acid, 2 parts of benzoyl peroxide, 1.5 parts of polyvinyl alcohol, 1.5 parts of wetting agent, 2 parts of defoaming agent, and 1.5 parts of chain extender; The particle size of the nano calcium oxide is 15 nm; the wetting agent is polyethylene glycol ether; the defoaming agent is pentaerythritol stearate; and the chain extender is diethyltoluenediamine.
[0030] The preparation method of the novel antibacterial composite material described in this comparative example comprises the following steps: (1) Weigh each raw material component according to the ratio, mix methyltriethoxysilane, half of anhydrous ethanol and deionized water under stirring at a speed of 40 r / min, then add citric acid and react at a temperature of 53°C for 2.5 hours, then add nano calcium oxide and continue to react for 2.5 hours, then add the remaining anhydrous ethanol and age for 9 hours to obtain a wet gel; (2) drying the wet gel obtained in step (1) at 60°C for 3.5h, then heating to 160°C at a rate of 3.5°C / min, then heating to 550°C at a rate of 1.5°C / min and keeping the temperature constant for 35min, and naturally cooling to room temperature to obtain an aerogel; (3) The aerogel, polypropylene, polyvinyl alcohol, wetting agent and defoaming agent obtained in step (2) are mixed uniformly, and then benzoyl peroxide and chain extender are added and mixed under stirring conditions at a speed of 250 r / min, and then sent to a twin-screw extruder for melt blending and extrusion, followed by cooling, air drying and granulation to obtain a novel antibacterial composite material; the extrusion temperature of the twin-screw extruder is 200° C. and the rotation speed is 450 r / min.
[0031] Experimental Example: An antibacterial composite material was prepared according to the method described in Examples 1 to 4 and Comparative Examples 1 to 3, and then the performance test was carried out according to standards ISO 527-2:2012 and QBT2591-2003 "Test method for antibacterial properties of antibacterial plastics". The specific results are shown in Table 1.
[0032] Table 1 Performance test results of antibacterial composite materials obtained by different methods
[0033] It can be seen from the above data that the composite material prepared according to the method of the present invention not only has excellent mechanical properties, but also has a high antibacterial rate, and the antibacterial effect is better than that of the composite material prepared using nano silver oxide (Comparative Example 1), and the effect obtained by the present invention is also significantly better than that of directly mixing nano calcium oxide and polypropylene (Comparative Example 2) or not adding sodium polyacrylate (Comparative Example 3).
[0034] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A novel antibacterial composite material, characterized in that: The invention comprises the following raw material components in parts by weight: 50-80 parts of polypropylene, 20-40 parts of nano calcium oxide, 10-20 parts of methyltriethoxysilane, 100-150 parts of anhydrous ethanol, 20-40 parts of deionized water, 2-5 parts of citric acid, 2-5 parts of sodium polyacrylate, 1-3 parts of benzoyl peroxide, 1-3 parts of polyvinyl alcohol, 1-3 parts of wetting agent, 1-3 parts of defoaming agent and 1-3 parts of chain extender.
2. The novel antibacterial composite material according to claim 1, characterized in that: The particle size of the nano calcium oxide is 10 to 30 nm.
3. The novel antibacterial composite material according to claim 1, characterized in that: The wetting agent is any one of polyethylene glycol ether and sodium dodecylbenzene sulfonate or a combination of two of them.
4. The novel antibacterial composite material according to claim 1, characterized in that: The defoaming agent is any one of pentaerythritol stearate and polyoxypropylene oxyethylene glycerol ether or a combination of two of them.
5. The novel antibacterial composite material according to claim 1, characterized in that: The chain extender is any one or more combinations of diethyltoluenediamine, glycidyl methacrylate and trimethylolpropane triacrylate.
6. The method for preparing the novel antibacterial composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Weighing each raw material component according to the ratio, mixing methyltriethoxysilane, half of anhydrous ethanol and deionized water under stirring conditions, then adding citric acid and reacting at a temperature of 50 to 60°C for 2 to 3 hours, then adding nano calcium oxide and sodium polyacrylate and continuing to react for 2 to 3 hours, then adding the remaining anhydrous ethanol and aging for 8 to 10 hours to obtain a wet gel; (2) drying the wet gel obtained in step (1) at 60° C. for 3 to 4 hours, then heating to 150 to 200° C. and keeping the temperature constant for 10 to 15 minutes, then heating to 500 to 600° C. and keeping the temperature constant for 30 to 45 minutes, and naturally cooling to room temperature to obtain an aerogel; (3) The aerogel, polypropylene, polyvinyl alcohol, wetting agent and defoaming agent obtained in step (2) are mixed evenly, and then benzoyl peroxide and chain extender are added, stirred and mixed, and then sent to a twin-screw extruder for melt blending and extrusion, followed by cooling, air drying and granulation to obtain a new antibacterial composite material.
7. The preparation method according to claim 6, characterized in that: The stirring speed in step (1) is 30 to 50 r / min.
8. The preparation method according to claim 6, characterized in that: In step (2), the temperature is heated to 150-200°C at a rate of 3-5°C / min, and then heated to 500-600°C at a rate of 1-3°C / min.
9. The preparation method according to claim 6, characterized in that: The stirring speed in step (3) is 200-300 r / min.
10. The preparation method according to claim 6, characterized in that: The extrusion temperature of the twin-screw extruder in step (3) is 180-220° C., and the rotation speed is 400-500 r / min.
Citation Information
Patent Citations
High strength antibacterial polypropylene composite material and preparation method thereof
CN103965544A
Thermal insulating EPDM / POE waterproof coiled material and preparation method thereof
CN106117831A
Shape memory polypropylene composite material containing aerogel for automobile bumper and preparation method thereof
CN106750980A
High-antibacterial low-emission automotive modified polypropylene composite material and preparation method thereof
CN109721844A
Preparation and application method of multifunctional environment-friendly formaldehyde-free resin wood impregnation modifier
CN110450252A